Analisis Pengaruh Persepsi Kemudahan dan Persepsi Kemanfaatan Penggunaan Google Classroom Terhadap Motivasi Belajar dan Kemandirian Belajar Siswa Pada Jurusan Multimedia Tahun Ajaran 2019/2020 (Studi Kasus: SMK Negeri 51 Jakarta Timur) - Kevin Maulana; Satrio Hadi Wijoyo; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The online learning policy that had to be taken during the Covid-19 pandemic required SMK Negeri 51 Timur to utilize learning media to facilitate learning and teaching activities to continue. One of the learning media used by SMK Negeri 51 East Jakarta is the Google Classroom. In the context of using Google Classroom as a computer technology, there are factors that affect the acceptance of technology use by users, one of which is the perception of convenience and the perception of usefulness. In this study, the authors tested the influence of the perceived ease of use factor and the perceived usefulness of using Google Classroom as a learning medium used by SMK 51 East Jakarta and how it affects student learning motivation and independence. This research was meant to determine whether there is a partial and simultaneous influence on the perceived ease of use and perceived usefulness of students in using Google Classroom on their learning motivation and learning independence. Researchers conducted observations, interviews and distributed questionnaires to collect primary data. The author uses a saturated sampling technique in taking samples or using the entire population of students in the multimedia department of the 2019/2020 school year totaling 72 students consisting of two classes. For data processing, the authors used partial test (t test), determination coefficient test, correlation product moment test, simple linear regression test and multiple linear regression test. After processing the data, the authors get the following results (1) perceived ease of use of Google Classroom has a partial effect on learning motivation as evidenced by the value of t count 4.066> t table 1.99444 with a significance value of 0.000 (2) perceived ease of use of Google Classroom has a partial effect on learning independence as evidenced by the value of t count 3,3456 > t count 1.99444 with a significance value of 0.001 (3) the perceived usefulness of using Google Classroom has a partial effect on learning motivation as evidenced by the value of t count 4,743> t table 1.99444 with a significance value of 0.000 (4) the perceived usefulness of using Google Classroom has a partial effect on learning independence as evidenced by the value of t count 5,319 > t table 1.99444 with a significance value of 0.000. (5) perceived ease of use and perceived usefulness of use have a simultaneous effect on learning motivation as evidenced by the value of f count 14.125> f tÂ table 3.13 with a significance value of 0.000. (6) perceived ease of use and perceived usefulness of use have a simultaneous effect on learning independence as evidenced by the value of f count 14.872> f t table 3.13 with a significance value of 0.000.